Relational Bureaucracy: Structuring Reciprocal Relationships into Roles - Gittell, Jody Hoffer; Douglass, Anne (Academy of Management Review, 2012)
We describe a hybrid relational bureaucratic form with structures that embed three processes of reciprocal interrelating—relational coproduction, relational coordination, and relational leadership—into the roles of customers, workers, and managers. We show how these role-based relationships of shared goals, shared knowledge, and mutual respect foster participants' attentiveness to the situation and to one another, enabling the caring, timely, and knowledgeable responses found in the relational form, along with the scalability, replicability, and sustainability found in the bureaucratic form. Through these role-based relationships, relational bureaucracy promotes universalistic norms of caring for particular others.